Haematuria: a long-term problem after prostatectomy. - Nargund, V; Noble, J; Cranston, D; Fellows, G (2001)
OBJECTIVE: The causes of 'late' haematuria (2 years or more) following endoscopic and open prostatectomy were studied. METHODS: Between 1994 and 1996, more than 400 patients were evaluated for haematuria. Ninety patients with post-prostatectomy haematuria were investigated with upper tract imaging and cystoscopic examination. Amongst these 90 patients, 30 presented with haematuria within 2 years of surgery. These patients were excluded from the study as they had normal investigations. RESULTS: Of these 60 patients, 24 (43%) had demonstrable causes of haematuria in their urinary tract. Six of them had urinary tract malignancy. CONCLUSIONS: There is a substantial likelihood of finding a cause for haematuria in patients who had prostatectomy even though they had full-scale urological investigations before. There is a need, therefore, to carry out necessary screening investigations in such patients.